(untitled) - 1940-; Smith, Douglas W.; 1960-; Duffy, Katy; Walker, Lauren E.; Landis, Bob (Princeton, 2023)
"A beautifully illustrated, large-format study of Yellowstone's birdlife, written by a team of renowned Park ornithologists and wildlife biologists"--
Includes bibliographical references and index.
Keywords: TRAVEL / United States / West / Mountain (AZ, CO, ID, MT, NM, NV, UT, WY); Ornithology; Yellowstone National Park; Birds; NATURE / Birdwatching Guides; Yellowstone National Park; Birds